Screening of drought-tolerant and sensitive genotypes in soybean (Glycine max L.) using different multivariate methods (International Journal of Agricultural Research, Innovation and Technology, 2018)
The soybean is a crop of global importance, which cultivate in worldwide. However, the soybean is more susceptible to water shortages during germination and reproductive growth stages. Stress is an in ordinary physical process of environmental factors effects and it has traumatic ability, which causes unusual metabolism in plants, and it is possible; reduce plant product or causes plant death. Drought indices provide a measure of drought based on loss of yield under drought conditions in comparison to normal and have been used for screening drought tolerant genotypes. We cultivated Ten genotypes of soybean in the research field of seed and plant improvement institute in Karaj- Iran in 2015 June. The experimental design was a randomized block with three replicate in two separate field experiments for normal and stress conditions. We irrigated the normal experiment in 85% field capacity and got 50% filed capacity for stress conditions. Seventeen drought tolerance indices were calculated. Four methods were used to identify more resistant and more susceptible genotypes. After genotypes selection, we carried out experiment in green house with two selected genotypes. Results showed using the indices such as MP, GMP and STI, alone, cannot select a stable genotype and we have to use a combine of all indices or use indices that showed reduction and average yield, together. In second year, results showed that we had a true selection.Int. J. Agril. Res. Innov. & Tech. 7 (2): 7-17, December, 2017